THE EFFECT OF CLIMATE FACTORS FOR DENGUE HEMORRHAGIC FEVER IN BANJARMASIN CITY, SOUTH KALIMANTAN PROVINCE, INDONESIA, 2012-2016 - Nuning Irnawulan Ishak; Kasman Kasman (Public Health of Indonesia)
Background: One of the factors that lead to high incidence of DHF is climate change.